Sodium dichloroisocyanurate: improving broiler health by reducing harmful microbial levels in the waterline - Zou, Qiangqiang; Meng, Weishuang; Wang, Chunqiang; Wang, Tieliang; Liu, Xiao; Li, Desheng (Frontiers in Veterinary Science, 2023)
Sodium dichloroisocyanurate (NaDCC) is commonly used for treating drinking water, industrial water, and wastewater. This study aimed to investigate the potential effects of NaDCC-treated waterline drinking water on the growth of AA+ broilers by reducing microbial levels in the waterline. A total of 480 healthy 1-day-old AA+ broilers (46.77 ± 0.50 g) were selected for the experiment and randomly divided into four groups with six replicates of 20 birds each. The control group received regular drinking water, while the test groups received drinking water with NaDCC concentrations of 10, 30, and 50 mg/L. The test groups consumed the treated water on specific days throughout the 42-day experimental period. Results showed that NaDCC treatment significantly reduced the levels of E. coli, Salmonella, S. aureus and Moulds in the drinking water at the waterline (p < 0.05). Drinking water with NaDCC also led to reduced broiler fecal emissions of NH3 and H2S, as well as reduced counts of E. coli, Salmonella, S. aureus and Moulds (p < 0.05), particularly at 30 mg/L and 50 mg/L concentrations. Broilers consuming NaDCC at 50 mg/L exhibited a significant increase in ADG from days 1–42 (p < 0.05). The levels of E. coli, Salmonella, S. aureus and Moulds in the drinking water at the waterline were significantly and positively correlated with the bacterial count in the feces (p < 0.05, R > 0.6). Additionally, bacterial levels in drinking water and broiler feces were negatively correlated with broiler production performance indicators, including ADG, ADFI, F/G and AWC. In conclusion, NaDCC can indirectly enhance broiler performance by reducing the levels of harmful bacteria in the waterline without affecting normal drinking water. The addition of 30 mg/L or 50 mg/L of NaDCC to the waterline in poultry production can effectively control harmful microorganisms and improve poultry health. Based on the experiment’s results, it is recommended to preferentially use 30 mg/L NaDCC in the waterline to reduce farming costs.